A Comparative Analysis of Art Fairs Based on the Resource-Based Theory —A Case Study of Frieze London and Frieze Seoul Art Fairs (Journal of Global Arts Studies, 2025)
Background: In recent years, the research on art fairs has gradually emerged as a focus of attention in the academic realm. Previous art fair research, mainly single-case or regional, lacks cross-national comparisons and strong theoretical grounding. This article endeavors to bridge this research gap by undertaking a systematic comparison of two significant art fairs, namely Frieze London and Frieze Seoul, from the perspective of the resource-based theory (RBV). Objective: This article uses Resource-Based Theory (RBV) to compare Frieze Seoul and Frieze London. It identifies similarities and differences in their core resources and capabilities, analyzing how policy environments, cultural characteristics, and market demands influence their resource integration strategies. Methods: Based on the RBV Theory, this paper employs a comparative case study approach to analyze the allocation of both tangible and intangible resources at Frieze London and Frieze Seoul. It investigates how these resource allocations impact their market performance and sustainable development, and further explores their respective resource allocation strategies and strategic implementation in diverse market environments. Results：A comparative study of Frieze London and Frieze Seoul reveals their distinct strengths. Frieze London maintains its global lead due to its rich art history, mature market, and extensive educational resources. Meanwhile, Frieze Seoul, bolstered by Korea's strong cultural industry, robust government support, and rising demand in emerging markets, shows strong growth and is becoming a key player in the Asian art market. Conclusion: The study finds that proactive policy support from the Korean government (e.g., tax incentives, cultural industry development plans) fosters a favorable environment for its art market. In contrast, London needs to optimize its art market competitiveness in the wake of post-Brexit policy adjustments. Furthermore, Frieze Seoul's success demonstrates that integrating local cultural traits and market demands can effectively boost art market development.
Keywords: Art Fairs; Frieze London; Frieze Seoul; Art Market